2017
DOI: 10.3390/ijms18030646
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Fish Let-7 MicroRNAs and Their Expression Correlated to Growth Development in Blunt Snout Bream

Abstract: Abstract:The lethal-7 (let-7) miRNA, known as one of the first founding miRNAs, is present in multiple copies in a genome and has diverse functions in animals. In this study, comparative genomic analysis of let-7 miRNAs members in fish species indicated that let-7 miRNA is a sequence conserved family in fish, while different species have the variable gene copy numbers. Among the ten members including let-7a/b/c/d/e/f/g/h/i/j, the let-7a precursor sequence was more similar to ancestral sequences, whereas other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 55 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…Five of the six identified miRNAs, namely miR-4792, let-7b-1, let-7b-2, miR-155-1, and miR-155-2, showed higher abundance in the M stage than in the FF stage ( Figure 5 ). Whereas let-7 is a well-studied miRNA belonging to the first founding miRNAs with possible roles in growth development (Kloosterman et al, 2004; Zhao et al, 2017), both miR-155 and miR-4792 have been examined less. Of the remaining miRNAs, miR-21 (ENSGACT00000028044.1) showed higher expression levels in the FF stage.…”
Section: Discussionmentioning
confidence: 99%
“…Five of the six identified miRNAs, namely miR-4792, let-7b-1, let-7b-2, miR-155-1, and miR-155-2, showed higher abundance in the M stage than in the FF stage ( Figure 5 ). Whereas let-7 is a well-studied miRNA belonging to the first founding miRNAs with possible roles in growth development (Kloosterman et al, 2004; Zhao et al, 2017), both miR-155 and miR-4792 have been examined less. Of the remaining miRNAs, miR-21 (ENSGACT00000028044.1) showed higher expression levels in the FF stage.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, numerous studies have indicated miRNA changes are associated with cancer biology, including cancer formation, development and metastasis ( 18 , 32 ). Let-7 miRNAs are underexpressed in the blood of patients with NSCLC ( 33 ) and expressed at lower levels in lung cancer ( 34 ). Similarly, the current results indicated that the expression of let-7a in lung adenocarcinoma tissues is reduced, suggesting that loss of let-7a may be a key factor in lung cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…So far, the miRNA-related studies had been reported in several fishes including zebrafish ( Danio rerio ), blunt snout bream ( Megalobrama amblycephala ), Botia superciliaris , and Pelteobagrus vachelli . These studies mainly pay attention to the regulatory role of miRNA in the growth (Zhao et al, 2017 ) and development of organs including the skeleton, gonad, skin, and liver (Gan et al, 2016 ; Zhang et al, 2016 ; Lan et al, 2019 ; Zhou et al, 2019 ). Nonetheless, there are few miRNA studies on fish IB development.…”
Section: Introductionmentioning
confidence: 99%